COURAGE IN HARPER LEE’S TO KILL A MOCKINGBIRD - Nadia Deibi Lambaiga; Mister Gidion Maru; Tirza Kumajas (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research is entitled Courage In Harper Lee’s To Kill A Mockingbird. The aim of this study is to find out the courage in the novel. Objective approach is applied in analysing the data to find out the courage in the novel. Qualitative research is descriptive. The data collected are in the form of words and pictures rather than numbers. The objective approach is applied because the analysis only focused on the novel itself. The results showed that the portrait of courage is detected through the reflections of the way that Atticus dare to defend blacks, and Atticus' attitude and actions who worked diligently and painstakingly to prove Tom Robinson's accusations untrue, This novel tries to demonstrate how the world and the people in it live a harmonious life together, through basic moral attitudes and actions, namely treating others with respect and kindness.